Optimalisasi Manajemen Perpustakaan Pasca Pandemi Covid 19 (Studi Di Perpustakaan UIN Tulungagung) - M. Ubaidillah Ridwanulloh; Melati Cahya Felani; Fatma Wulan Maulidiyah; Ayuni Maratus Sholihah; Ardiana Fatma Dewi (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
This study aims to analyze library management recovery strategies following the COVID-19 pandemic and to examine how these strategies support library sustainability across diverse contexts. The study used a qualitative case study approach conducted at the UIN Sayyid Ali Rahmatullah Tulungagung Library. Research informants included the library head, librarians, administrative staff, and users. Data were collected through observation, in-depth interviews, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing. The results show that library management recovery strategies are implemented through sustainable program planning, innovation in collection procurement, strengthening digital and conventional services, increasing librarian capacity, implementing information literacy programs, and promoting services through social media and academic activities. The implementation of these strategies has resulted in increased user visits, reduced service complaints, and increased user satisfaction. The research findings confirm that the success of library management recovery is determined not only by the ability to restore post-crisis services, but also by the ability to adapt to environmental changes, strengthen human resources, integrate information technology, and build responsive and sustainable governance. This research contributes to the development of library management studies by offering a conceptual model of management recovery that integrates aspects of service, human resources, technology, and promotion as a library sustainability strategy to address various crisis conditions and future environmental changes.